The Peace-Athabasca Delta : portrait of a dynamic ecosystem - Timoney, Kevin P. (Kevin Patrick), 1955- (University of Alberta Press, 2013)
Timely ecology of the Peace-Athabasca Delta, the threatened home of wildlife and Indigenous cultures.